2016
DOI: 10.17060/ijodaep.2014.n1.v5.692
|View full text |Cite
|
Sign up to set email alerts
|

La Comunicación Familiar en La Victimización Del Bullying Y El Cyberbullying

Abstract: Bullying is now out of the school through the technologies of information and communication. For this reason, researchers are now analyzing two phenomena related with peer harassment: bullying and cyberbullying. Several studies have pointed out the importance of family communication in bullying behaviors. Indeed, previous research has shown that open communication between parents and children is a protective factor against victimization in bullying. Research analyzing the influence of family communication in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…On the contrary, good communication works as a protective factor, reducing the risk of becoming a cybervictim. Several previous studies (e.g., Varela 2012;Yubero et al 2014) found a greater possibility of becoming a victim of cyberbullying when there are, in general, communication problems in the family and, in particular, when we refer to the relationship with the mother. Therefore, the authors agree with Yubero et al (2014, p. 344) on the importance of "improving family communication to protect children from harassment".…”
Section: Parent-child Communicationmentioning
confidence: 82%
“…On the contrary, good communication works as a protective factor, reducing the risk of becoming a cybervictim. Several previous studies (e.g., Varela 2012;Yubero et al 2014) found a greater possibility of becoming a victim of cyberbullying when there are, in general, communication problems in the family and, in particular, when we refer to the relationship with the mother. Therefore, the authors agree with Yubero et al (2014, p. 344) on the importance of "improving family communication to protect children from harassment".…”
Section: Parent-child Communicationmentioning
confidence: 82%